Karakterisasi Cabai Merah Giling yang Disimpan dalam Media Kolam Ikan Masyarakat Di Kota Padang Sumatera Barat - Nanda, Ririn Fatma; Yenrina, Rina; Yolanda, Milda; Azima, Fauzan; Syukri, Daimon (JURNAL BIOSENSE, 2023)
Storing ground chilies in fish ponds was initiated by the Padang City, West Sumatra Province community. This research aimed to determine the characteristics of ground red chilies stored in fish ponds and refrigerators. 100 g of ground chili was stored and packaged in low-density polyethylene (LDPE) plastic clips and again in polypropylene (PP) plastic clips. The packaged material was soaked in a fish pond to a depth of ± 60 cm. Some packaged chilies were also stored in the refrigerator at ± 6 oC. Observations on the quality of ground chili, including water content, total titrated acid, antioxidant activity, air activity, total plate number, and organoleptic were analyzed periodically for ten weeks. The results showed that until the 10th week of storage, the characteristics of ground red chilies stored in fish ponds were almost identical to those stored in the refrigerator. The storage temperature in a fish pond differed from that in a refrigerator. Based on these findings, it can be hypothesized that a Modified Atmospheric Packaging system has occurred during storage in fish ponds because it allows low temperatures, which can slow down the freezing process. Therefore, further research needs to be conducted to assess the potential of fish ponds as an environmentally friendly storage place for fresh chilies. Keyword: storage, society, water media, ecosystem